RESPONS TANAMAN JAGUNG MANIS (Zea mays saccharata L.)TERHADAP PEMBERIAN PUPUK ORGANIK - Antonius R. Kuyik; Pemmy Tumewu; Doortje M.F. Sumampow; Antje G. Tulungen (COCOS, 2013)
ABSTRACT This research aims to study response of sweet corn plants (Zea mays saccharata L.) that were fertilized with organic fertilizer. The research was implemented in green house of Agriculture Faculty, Sam Ratulangi University of Manado, on July to November 2012. The result of research as follow : Height of plants on D treatment (15 tons of stable fertilizer per hectare + 750 kilograms of granul organic fertilizer per hectare) gave best respons, Number of leaves on C treatment (15 tons of stable fertilizer per hectare + 500 kilograms of granul organic fertilizer per hectare ) and D treatment ( 15 tons of stable fertilizer per hectare + 750 kilograms of granul organic fertilizer per hectare) gave best response. Result of sweet corn that were measured by length, diameter and weight of corn cob on B treatment (anorganic fertilizer of N, P and K with recommended doses N 300 kg per hectare, P 150 per hectare, P 150 kg per hectare, and K 150 kg per hectare) gave best response. Keywords :sweet corn, organic fertilizer